Current determinants of the national accounting system transformation in Iraq - K.S.A. Ahmed; A. K. Musaelyan; M. V. Krasnoplakhtich (Вестник университета)
The article examines the most relevant issues of the external and internal factors’ influence on the accounting current development in Iraq. Historically, Iraq’s accounting system has been shaped by cultural traditions, religion, economic development and political trends over a long period, from ancient times to the present. Its origins date back to the Sumerian kingdom and before the overthrow of the S. Hussein regime. At present, not only national priorities but also global accounting trends have changed. Being formed in parallel with the development of the Republic of Iraq, the current accounting system is not oriented towards the requirements of International Financial Reporting Standards. In order to identify the current determinants of the national accounting system development, the actual model features and the conditions for consolidation with international standards have been analysed. The main directions of accounting harmonisation in the Republic of Iraq towards the international standards integration into the national system have been identified. The main steps of the transformation of national standards to international standards have been presented.